KUALITAS PELAYANAN ONLINE SINGLE SUBMISSION (OSS) PADA DINAS PENANAMANAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KOTA PEKANBARU - Chandra Wijaya; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study discusses the Quality of Online Single Submission (OSS) Services at the Pekanbaru City Investment and One Stop Integrated Service (DPMTSP). The quality of the Online Single Submission (OSS) service is an undoubted strategy to support the role of the One Stop Integrated Service and Investment Service (DPMTSP) in providing administrative services to the community.This study uses a service perspective, public service, and the principles of public service. In carrying out its roles and functions, the Online Single Submission (OSS) as part of public services shows a good level of quality and is in accordance with the values and principles of public service. Quality Online Single Submission (OSS) services contribute to the acceleration of the public service process at the Pekanbaru City Investment and One Stop Integrated Service (DPMTSP). The resulting quality will affect public satisfaction and the acceleration of the administrative process which is expected through the breakthrough of the One-Stop Integrated Service and Investment Service (DPMTSP). Keywords: Online Single Submission, DPMTSP, Public Service, Service Quality